-3x - 4y - 3z = -7
5x - 2y + 5z = 9.....multiply by -2
-------------------
-3x - 4y - 3z = -7
-10x + 4y - 10z = -18 (result of multiplying by -2)
-----------------add
-13x - 13z = - 25
2x - 6y + 2z = 3
5x - 2y + 5z = 9....multiply by -3
-------------------
2x - 6y + 2z = 3
-15x + 6y - 15z = -27 (result of multiplying by -3)
-------------------add
-13x - 13z = - 24
-13x - 13z = -25...multiply by -1
-13x - 13z = -24
---------------------
13x + 13z = 25 (result of multiplying by -1)
-13x - 13z = -24
--------------------add
0 = 1....incorrect......NO SOLUTION